2015
DOI: 10.1016/j.cemconres.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of moisture transfers with hysteresis within cementitious materials: Verification and investigation of the effects of repeated wetting–drying boundary conditions

Abstract: a b s t r a c tIn natural environment, the cover layer of reinforced concrete structures is affected by periodic variations of external relative humidity (RH). However, most moisture transport models in the literature only focus on drying of materials. In this study, a method coupling a moisture transport model with any kind of hysteresis modelling is presented. Two hysteresis models (conceptual and empirical) have been implemented and compared. The scope of the study is limited to cyclic variations of RH with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 56 publications
1
51
0
1
Order By: Relevance
“…Qualitatively, we found that K l plays the main role for the calculation of mass loss curves while x D has very limited influence. This is in agreement with results in previous studies where the mass loss curves were generally used to inversely determine K l [32,33,34,51,18,36,20]. Adjusting the value of x D can however improve the shape of saturation profiles determined by gamma-ray attenuation (see Fig.…”
Section: Experimental Data and Fitting Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Qualitatively, we found that K l plays the main role for the calculation of mass loss curves while x D has very limited influence. This is in agreement with results in previous studies where the mass loss curves were generally used to inversely determine K l [32,33,34,51,18,36,20]. Adjusting the value of x D can however improve the shape of saturation profiles determined by gamma-ray attenuation (see Fig.…”
Section: Experimental Data and Fitting Resultssupporting
confidence: 81%
“…Consequently, the following fitting procedure has been adopted here. First, we let x D = 2.74 (commonly-used value in previous studies [27,34,51,18,36,20]) to fit the measured drying kinetics by adjusting K l . Second, we change the value of x D to optimize the fitting of gamma-ray saturation profile at a given time of drying.…”
Section: Experimental Data and Fitting Resultsmentioning
confidence: 99%
See 3 more Smart Citations